1997
DOI: 10.1111/j.1398-9995.1997.tb01046.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein and allergen content of various natural latex articles

Abstract: Proteins remaining in products made of natural rubber latex are potential sensitizers. In the present work, we quantified the releasable protein and allergen contents in 37 brands of latex gloves and 26 other latex products. Our results demonstrate the presence of widely varied protein and allergen contents in various latex articles and the lack of a correlation between the protein and allergen values. These findings may assist hospital management and medical staff to take effective preventive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 21 publications
0
27
0
4
Order By: Relevance
“…The manufacturing process may lead to denaturing of proteins in raw latex, and it has been reported that the allergen profiles differed between finished products and the raw materials [25, 26]. Previous studies also documented that the total protein level does not necessarily correlate with the allergen content [24, 27, 28]. There was no known ‘safety margin’ for the level of total latex protein with regard to the allergenicity of latex gloves, unless we measure the true IgE-binding allergen directly.…”
Section: Discussionmentioning
confidence: 99%
“…The manufacturing process may lead to denaturing of proteins in raw latex, and it has been reported that the allergen profiles differed between finished products and the raw materials [25, 26]. Previous studies also documented that the total protein level does not necessarily correlate with the allergen content [24, 27, 28]. There was no known ‘safety margin’ for the level of total latex protein with regard to the allergenicity of latex gloves, unless we measure the true IgE-binding allergen directly.…”
Section: Discussionmentioning
confidence: 99%
“…Studien beschrieben eine Prävalenz der Sensibilisierung gegen Naturlatex im medizinischen Berufen von bis zu 17% [7]. Hauptallergenträger sind gepuderte Latexhandschuhe [2,6]. Die Zahl der bestätigten BK 5101-Fälle stieg von etwa 300 im Jahr 1995 auf etwa 900 im Jahr 1998.…”
Section: Hintergrund Und Fragestellungunclassified
“…Extracts from latex products were prepared according to the method of Baur et al [9]. Briefly, 5 g of NRL glove materials were cut into small pieces (approximately 1–2 cm 2 ) and extracted in PBS (pH 7.4) by shaking for 2 h at 37°C (5 g of latex glove material in 50 ml of extraction buffer).…”
Section: Methodsmentioning
confidence: 99%